Sêrat Bayanolah: Naskah Jawa sebagai Sarana Pelurusan Penyimpangan Akidah Islam Karya Raden Panji Natarata - Rahmawati, Mila Indah; Rais, Wakit Abdullah; Wisnu Wibowo, Prasetyo Adi (Sutasoma : Jurnal Sastra Jawa, 2021)
Abstract Javanese literary works are considered as high-quality literary works. This is closely related to the noble values ​​contained in Javanese literary works. The teachings or noble values ​​in this Javanese literary work are usually referred to as piwulang literary works, namely works that originate from religious values ​​or teachings that come from God. One of the Javanese literary works with piwulang nuances is Sêrat Bayanolah. This work tells about the journey of a panatagama at the Yogyakarta Palace in discovering the true essence of life. To understand this concept is not easy because in reality there are many deviant schools of thought and religion which can derail people from the right path. This research was conducted in a descriptive qualitative manner. The data source used was Sêrat Bayanolah by Raden Panji Natarata, which was collected by the Museum of Reksa Pustaka Pura Mangkunegaran, Surakarta. Based on the research results, it was found that the essence of man as a creature is not the same as the essence of God (God) as the Creator. Besides, interpreting the concept of life and death must be adjusted to Islamic teachings because in reality there are still scholars and knowledgeable people who still misunderstand the concept of life and death. Keywords: Sêrat Bayanolah, Javanese script, deviations, faith